Voluntary exercise does not increase gastrointestinal motility but increases spatial memory, intestinal eNOS, Akt levels, and Bifidobacteria abundance in the microbiome - Bakonyi, Peter; Kolonics, Attila; Aczel, Dora; Zhou, Lei; Mozaffaritabar, Soroosh; Molnár, Kinga; László, Lajos; Kutasi, Balazs; Tanisawa, Kumpei; Park, Jonguk; Gu, Yaodong; Pinho, Ricardo A.; et al. (Frontiers in Physiology, 2023)
The interaction between the gut and brain is a great puzzle since it is mediated by very complex mechanisms. Therefore, the possible interactions of the brain–exercise–intestine–microbiome axis were investigated in a control (C, N = 6) and voluntarily exercised (VE, N = 8) middle-aged rats. The endurance capacity was assessed by VO2max on the treadmill, spatial memory by the Morris maze test, gastrointestinal motility by EMG, the microbiome by 16S RNA gene amplicon sequencing, caveolae by electron microscopy, and biochemical assays were used to measure protein levels and production of reactive oxygen species (ROS). Eight weeks of voluntary running increased VO2max, and spatial memory was assessed by the Morris maze test but did not significantly change the motility of the gastrointestinal tract or production of ROS in the intestine. The protein kinase B (Akt) and endothelial nitric oxide synthase (eNOS) protein levels significantly increased in the intestine, while peroxisome proliferator–activated receptor gamma coactivator 1 alpha (PGC-1α), mitochondrial transcription factor A (TFAM), nuclear respiratory factor 1 (NFR1), SIRT1, SIRT3, nicotinamide phosphoribosyl transferase (NAMPT), and nuclear factor κB (NF-κB) did not change. On the other hand, voluntary exercise increased the number of caveolae in the smooth muscles of the intestine and relative abundance of Bifidobacteria in the microbiome, which correlated with the Akt levels in the intestine. Voluntary exercise has systemic effects and the relationship between intestinal Akt and the microbiome of the gastrointestinal tract could be an important adaptive response.